2022
DOI: 10.1093/cvr/cvac036
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial OCT4 is atheroprotective by preventing metabolic and phenotypic dysfunction

Abstract: Aims Until recently, the pluripotency factor OCT4 was believed to be dispensable in adult somatic cells. However, our recent studies provided clear evidence that OCT4 has a critical atheroprotective role in smooth muscle cells (SMC). Here, we asked if OCT4 might play a functional role in regulating endothelial cell (EC) phenotypic modulations in atherosclerosis. Methods and Results Specifically, we show that EC-specific Oct4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…In this study, we reanalyzed some data generated in our previous publications. Specifically, EC-lineage tracing mice ( Cdh5 -CreERT2 [Tg(Cdh5-cre/ERT2)1Rha] mice, Rosa-Stop-eYFP [B6.129X1- GT(ROSA)26Sor tm1(EYFP)Cos ], Apoe –/– [B6.129P2- Apoe tm1Unc ]) were generated by our group as described in Shin et al 22 We reanalyzed results from Shin et al using control ( Oct4 wild type) EC-lineage tracing Apoe –/– mice to generate new results, specifically comparing male versus female mice for the physiological parameters (Table S1), lesion morphometry (see Figure 4C through 4G; Figure S4), and EC-lineage tracing quantification (see Figure 5D through 5F). Also, we used tissues from the control male and female mice from Shin et al to generate new data (see Figure 5A through 5C and 5H through 5K).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we reanalyzed some data generated in our previous publications. Specifically, EC-lineage tracing mice ( Cdh5 -CreERT2 [Tg(Cdh5-cre/ERT2)1Rha] mice, Rosa-Stop-eYFP [B6.129X1- GT(ROSA)26Sor tm1(EYFP)Cos ], Apoe –/– [B6.129P2- Apoe tm1Unc ]) were generated by our group as described in Shin et al 22 We reanalyzed results from Shin et al using control ( Oct4 wild type) EC-lineage tracing Apoe –/– mice to generate new results, specifically comparing male versus female mice for the physiological parameters (Table S1), lesion morphometry (see Figure 4C through 4G; Figure S4), and EC-lineage tracing quantification (see Figure 5D through 5F). Also, we used tissues from the control male and female mice from Shin et al to generate new data (see Figure 5A through 5C and 5H through 5K).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies from our and other labs utilizing cellspecific lineage tracing Apoe -/mouse models have shown that vascular cells, including smooth muscle cell, [17][18][19] EC, [20][21][22] and macrophages (MФ) undergo phenotypic transitions when they undertake properties and lineage markers of other cell types, and these transitions can play atheroprotective or atheropromoting roles. However, the cell type-specific sex differences of atherosclerosis development are still unknown.…”
mentioning
confidence: 99%
“…The immune system plays a crucial role in the development and progression of atherosclerotic lesions 4,5 . The plaque microenvironment contains pro‐inflammatory cytokines, oxidized lipids, cholesterol crystals, oxidative stress markers, and danger‐associated molecular patterns that trigger macrophage activation 6,7 . Macrophages perform a wide range of functions, ranging from phagocytosing apoptotic cells and pathogens to releasing immune effector molecules.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The plaque microenvironment contains pro-inflammatory cytokines, oxidized lipids, cholesterol crystals, oxidative stress markers, and dangerassociated molecular patterns that trigger macrophage activation. 6,7 Macrophages perform a wide range of functions, ranging from phagocytosing apoptotic cells and pathogens to releasing immune effector molecules. Stimulation from the environment can influence macrophage phenotypes and cause them to change their function.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research from the Cleveland Clinic illustrated that the ATP transporter, ABCG2, is a direct target of OCT4 in endothelial cells and established for the first time that the OCT4/ABCG2 axis maintains endothelial metabolic homeostasis by regulating intracellular heme accumulation and ROS production. 38 Interestingly, there is evidence suggesting that OCT4 expression varies during the development of atheromatosis. During the early phases of proatherogenic inflammation, OCT4 appears to be upregulated in VSMCs and VSMC-derived phagocytic cells.…”
Section: The Role Of Oct4 In Atheromatosismentioning
confidence: 99%